The Role of Human Rights and Customary Law to Prevent Early Childhood Marriage in Indonesia - Anak Agung Istri Ari Atu Dewi; Ni Ketut Supasti Dharmawan; Anak Agung Istri Eka Krisnayanti; Putu Aras Samsithawrati; I Gede Agus Kurniawan (Faculty of Law, Sriwijaya University, Indonesia, 2022)
Preventing early childhood marriage (ECM) can protect children’s rights from the perspective of human rights. There are several rules regarding the age limit for marriage. In Indonesia, the minimum age for marriage is nineteen years. However, in fact, early child marriage is still relatively high, with the seventh highest ranking in the world. This study aims to elaborate on the rights of children, which ECM potentially violates, and to identify who is responsible for minimizing and/or combating this phenomenon. This normative legal research with a human rights approach occurs in the childhood protection context. The results show that ECM has implications for violations against the right to life, the right to education, the right to develop, and the right to health. Thus, more stringently applying international and national law and combining with local wisdom (Balinese Customary Law) in protecting children's rights in the context of preventing ECM can prevent ECM effectively and minimize violations of other children's rights. Moreover, it is believed that the responsibility to reduce and combat ECM not only belongs to the government but also to all stakeholders within the community, such as families, academics, the media, non-profit organizations, entrepreneurs, and customary.